Negative DAT‐SPECT in Old Onset Parkinson's Disease: An Additional Pitfall?. Issue 4 (15th April 2022) - Palermo, Giovanni; Giannoni, Sara; Depalo, Tommaso; Frosini, Daniela; Volterrani, Duccio; Siciliano, Gabriele; Bonuccelli, Ubaldo; Ceravolo, Roberto
ABSTRACT: Background: Scans without evidence of dopaminergic deficit (SWEDDs) refer to patients clinically diagnosed with Parkinson's disease (PD), but showing normal findings on dopamine transporter single‐photon emission computed tomography (DAT‐SPECT). This entity remains highly debated, but recent findings suggesting that DAT‐SPECT does not reflect either nigral cell bodies or striatal fibers of dopaminergic nigrostriatal neurons could improve our understanding of SWEDDs. Notably, compensatory downregulation of DAT in the early stages of PD seems to be less efficient in older‐onset than in young‐onset patients. Cases: We report eight patients with old‐onset clinical parkinsonism and a positive response to levodopa in which DAT‐SPECT was normal both visually and semiquantitatively. Two subjects demonstrated an abnormal scan when repeated later. Conclusions: We suggest that old‐onset patients may truly have dopaminergic degeneration despite normal imaging results, presumably because they are diagnosed in the early stages confirming less efficient striatal compensatory strategies in old‐age onset PD.